A negative electrode material, a preparation method thereof and a lithium battery

CN122950446APending Publication Date: 2026-10-20HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611195514.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

现有技术往往存在掺杂元素分布不均、过渡金属易团聚、与硅界面结合弱等问题

Benefits of technology

S1.将木质素磺酸钠溶解于去离子水中,再加入过渡金属盐、氮源、硼源,混合均匀,得到前驱体溶液;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention relates to the field of battery technology, specifically disclosing an anode material, its preparation method, and a lithium battery. The anode material comprises a three-dimensional carbon network framework and core-shell particles embedded within the three-dimensional carbon network framework. The core-shell particles comprise a nano-silicon core and a porous carbon shell layer covering the nano-silicon core. The porous carbon layer contains doping elements, including transition metals, nitrogen, boron, and sulfur. This invention uses a three-dimensional carbon network as a supporting framework, with core-shell particles embedded within, forming a silicon-carbon composite material with a multi-level porous structure, strong interfacial bonding, and abundant active sites. The porous carbon layer employs a multi-element synergistic doping system to construct a transition metal-N-B-S multi-element doped carbon framework, where the functions of each element are complementary, improving the performance of the anode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to a negative electrode material, its preparation method, and a lithium battery. Background Technology

[0002] With the rapid development of electric vehicles and large-scale energy storage, the development of high-energy-density, long-cycle-life lithium-ion battery anode materials has become a research hotspot. Silicon-based materials have a theoretical capacity as high as 4200 mAh / g, but their huge volume expansion (>300%) leads to electrode structure damage and a sharp decline in cycle life. Existing technologies mostly use carbon material coating and multi-element doping to alleviate volume expansion and improve conductivity.

[0003] Sodium lignosulfonate, a byproduct of the papermaking industry, is produced in large quantities and is inexpensive. Its molecular structure contains both a benzene ring framework and sulfonic acid groups, making it an ideal carbon source and a natural sulfur source. However, current utilization of sodium lignosulfonate is mostly limited to simple carbonization, failing to fully realize its potential as a multi-element doped carbon precursor.

[0004] Transition metal-nitrogen-carbon (MNC) materials exhibit excellent catalytic activity in areas such as oxygen reduction, but their application in lithium-ion battery anodes is relatively limited. Studies have shown that MNCs formed by transition metals (Fe, Co, Ni, etc.) and heteroatoms such as nitrogen and sulfur can... x S y Coordination structures not only significantly improve electronic conductivity but also catalyze lithium-ion conversion reactions and improve electrode reaction kinetics. Simultaneously, the introduction of boron can modulate the electronic structure of carbon materials, forming a pn synergistic effect. Existing technologies often suffer from problems such as uneven distribution of dopant elements, easy agglomeration of transition metals, and weak bonding with the silicon interface. Summary of the Invention

[0005] Based on this, the purpose of this invention is to provide an anode material, its preparation method, and a lithium battery, which organically combines the natural advantages of sodium lignosulfonate with various doping elements (especially transition metals) to construct a silicon-carbon composite material with a hierarchical porous structure, strong interfacial bonding, and abundant active sites.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: The present invention provides an anode material comprising a three-dimensional carbon network framework and core-shell particles embedded in the three-dimensional carbon network framework. The core-shell particles comprise a nano-silicon core and a porous carbon shell layer covering the nano-silicon core. The porous carbon layer contains transition metal, nitrogen, boron and sulfur dopants.

[0007] The anode material provided by this invention uses a three-dimensional carbon network as a supporting framework, with core-shell particles embedded in it. The porous carbon layer adopts a multi-element synergistic doping system to construct a transition metal-NBS multi-element doped carbon framework, with each element having complementary functions. The transition metal catalytic active center improves reaction kinetics, and the introduction of transition metal iron can significantly improve the electrochemical performance of the material. Nitrogen provides electron donors and forms M-Nx active sites with the transition metal. Boron acts as an electron acceptor and forms pn synergy with nitrogen to regulate the electronic structure. Sulfur can expand the carbon layer spacing and enhance electrolyte wetting, thereby improving the performance of the anode material.

[0008] As a further improvement to the above-described scheme of the present invention, both the three-dimensional carbon network framework and the porous carbon shell are formed by the pyrolysis of sodium lignosulfonate. Sodium lignosulfonate possesses both an aromatic framework and sulfonic acid groups, and during pyrolysis, it can directly form a conductive carbon network rich in defect and heteroatom doping sites. Simultaneously, the sulfonic acid groups can serve as a natural sulfur source to achieve uniform sulfur doping. The uniform distribution of carbon and sulfur elements at the molecular scale in sodium lignosulfonate is more conducive to the formation of a stable NBS co-doped structure. Furthermore, sodium lignosulfonate has a strong dispersing effect, which can effectively inhibit the aggregation of nano-silicon and improve the uniformity of carbon layer coating.

[0009] As a further improvement to the above-described solution of the present invention, the transition metal is at least one of iron, cobalt, and nickel, and the transition metal is mainly composed of MN. x Coordination forms exist, where M represents a transition metal and x = 2~4.

[0010] As a further improvement to the above-described scheme of the present invention, in the porous carbon layer, nitrogen element is pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen and MN. x It exists in four forms, among which MN x It accounts for 20% to 50% of the total nitrogen content.

[0011] As a further improvement to the above-mentioned scheme of the present invention, the content of each doping element in the porous carbon layer is: transition metal 1 at.%~5 at.%, nitrogen 3 at.%~10 at.%, boron 1 at.%~4 at.%, sulfur 1 at.%~3 at.%.

[0012] As a further improvement to the above-mentioned scheme of the present invention, the particle size of the nano-silicon is 50~200 nm, and the thickness of the porous carbon layer is 5~20 nm.

[0013] As a further improvement to the above-described scheme of the present invention, the specific surface area of ​​the negative electrode material is 300~800 m². 2 / g, pore volume 0.8~2.5 cm³ 3 / g; and / or, the porous carbon layer has a three-level pore structure: micropores with a pore size <2 nm account for 15%-30% of the volume, mesopores with a pore size of 2~50 nm account for 50%~75% of the volume, and macropores with a pore size >50 nm account for 10%~25% of the volume.

[0014] The present invention also provides a method for preparing the negative electrode material as described above, which includes the following steps: S1. Dissolve sodium lignosulfonate in deionized water, then add transition metal salt, nitrogen source, and boron source, mix well to obtain precursor solution; S2. After functionalizing nano-silicon with amino or carboxyl groups, add it to the precursor solution, add a ligand, adjust the pH, and carry out a coordination self-assembly reaction to form a composite gel. S3. After heat treatment, the composite gel is pyrolyzed, acid-washed, and post-treated to obtain the negative electrode material.

[0015] This invention utilizes sodium lignosulfonate as both a carbon and sulfur source, introducing transition metals, nitrogen, and boron co-doping through molecular design to prepare high-performance silicon-carbon composite anode materials. Sodium lignosulfonate serves as a multifunctional precursor, possessing both an aromatic framework and sulfonic acid groups. During pyrolysis, it directly forms a conductive carbon network rich in defect and heteroatom doping sites. Simultaneously, the sulfonic acid groups act as a natural sulfur source, achieving uniform sulfur doping. Compared to systems where glucose and sodium sulfate provide the carbon and sulfur sources respectively, the carbon and sulfur elements in sodium lignosulfonate are uniformly distributed at the molecular scale, which is more conducive to forming a stable NBS co-doped structure. Furthermore, sodium lignosulfonate has a strong dispersing effect, effectively inhibiting nano-silicon agglomeration and improving the uniformity of carbon layer coating. Utilizing the pyrolysis characteristics of sodium lignosulfonate, a microporous-mesoporous-macroporous hierarchical structure is formed. In-situ growth and strong interfacial bonding: through surface hydroxylation and silane coupling agent modification, a covalently bonded interface is constructed on the nano-silicon surface. Molecular-level mixing and coordination of elements are achieved in the solution stage, realizing in-situ coordinated doping. This invention uses an aqueous system, which is suitable for industrial production.

[0016] In the coordination self-assembly process of this invention, transition metal ions can simultaneously undergo synergistic coordination with the hydroxyl, carboxyl, and sulfonic acid groups in sodium lignosulfonate, as well as the amino groups on the surface of nano-silicon, forming a uniform and stable three-dimensional network structure. Subsequent pyrolysis yields a porous doped carbon layer continuously coated on the surface of nano-silicon, achieving uniform dispersion of transition metal active sites.

[0017] As a further improvement to the above-described scheme of the present invention, in step S1, the mass ratio of sodium lignosulfonate, transition metal, nitrogen source, and boron source is 1:(0.05~0.3):(0.2~0.8):(0.05~0.2).

[0018] As a further improvement to the above-described solution of the present invention, the transition metal salt is selected from at least one of ferric chloride, ferric nitrate, ferrous sulfate, cobalt chloride, cobalt nitrate, nickel chloride, and nickel nitrate. And / or, the nitrogen source is at least one of melamine, urea, dicyandiamide, and polyaniline; And / or, the boron source is at least one of boric acid, borax, and phenylboronic acid.

[0019] As a further improvement to the above-mentioned scheme of the present invention, in step S2, the functionalization includes: hydroxylating nano-silicon to obtain hydroxylated nano-silicon, dispersing the hydroxylated nano-silicon in a solvent, adding a silane coupling agent, reacting at 50~80℃ for 4~8h under a protective atmosphere, and then post-processing to obtain amino or carboxyl functionalized nano-silicon; the silane coupling agent is γ-aminopropyltriethoxysilane or γ-carboxyethylsilane triol sodium salt.

[0020] As a further improvement to the above-described scheme of the present invention, the coordinating agent is ethylenediaminetetraacetic acid or citric acid; the pH adjustment is to adjust the pH to 4-7; and the coordination self-assembly reaction is carried out by stirring at 60-90°C for 2-5 hours. Through the coordination self-assembly reaction, transition metal ions form coordination bonds with the functional groups in sodium lignosulfonate and the surface groups of nano-silicon.

[0021] As a further improvement to the above-mentioned scheme of the present invention, in step S3, the heat treatment is performed at 80~120℃ for 2~6 hours; the pyrolysis is performed by first heating to 400~600℃ at 2~5℃ / min for pre-carbonization for 1~3 hours, and then heating to 700~1000℃ at 5~10℃ / min for carbonization for 2~4 hours. The present invention adopts a stepwise pyrolysis strategy, with low-temperature pre-crosslinking to fix the doping elements and high-temperature carbonization to form a stable structure.

[0022] The present invention also provides a lithium battery comprising the negative electrode material as described above.

[0023] As a further improvement of the above-mentioned solution of the present invention, the lithium battery has an initial discharge specific capacity of ≥1800 mAh / g and an initial coulombic efficiency of ≥83% at 0.1C rate; a capacity retention rate of ≥85% after 800 cycles at 1C rate; and a capacity retention rate of ≥70% at 5C rate.

[0024] The negative electrode material of this invention, after being compounded with graphite to a specific capacity of 500 mAh / g, is applied to a 4Ah soft-pack battery with an energy density ≥280 Wh / kg. Attached Figure Description

[0025] Figure 1 This is a flowchart of a method for preparing a negative electrode material provided by the present invention. Detailed Implementation

[0026] To facilitate understanding of the present invention, a more comprehensive description will be given below with reference to specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of the present invention.

[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0028] As described in the background section of this application, current anode materials often suffer from problems such as uneven distribution of doped elements, easy agglomeration of transition metals, and weak bonding with silicon at the interface. To address these issues, this application provides an anode material, its preparation method, and a lithium battery.

[0029] In a first typical embodiment of this application, an anode material is provided, which includes a three-dimensional carbon network framework and core-shell particles embedded in the three-dimensional carbon network framework. The core-shell particles include a nano-silicon core and a porous carbon shell layer covering the nano-silicon core. The porous carbon layer contains transition metal, nitrogen, boron and sulfur dopants.

[0030] This anode material uses a three-dimensional carbon network as its supporting framework, with core-shell particles embedded within. The porous carbon layers employ a multi-element synergistic doping system to construct a transition metal-NBS multi-element doped carbon framework, where each element has complementary functions. The transition metal catalytic active center improves reaction kinetics, and the introduction of transition metal iron can significantly improve the electrochemical performance of the material. Nitrogen provides electron donors and forms M-Nx active sites with the transition metal. Boron acts as an electron acceptor and forms pn synergy with nitrogen to regulate the electronic structure. Sulfur can expand the carbon layer spacing and enhance electrolyte wetting.

[0031] In another embodiment, the three-dimensional carbon network framework of the negative electrode material and the porous carbon shell of the core-shell particles are both formed by the pyrolysis of sodium lignosulfonate. Sodium lignosulfonate possesses both an aromatic framework and sulfonic acid groups, which can directly form a conductive carbon network rich in defect and heteroatom doping sites during pyrolysis. Simultaneously, the sulfonic acid groups can serve as a natural sulfur source to achieve uniform sulfur doping. The uniform distribution of carbon and sulfur elements at the molecular scale in sodium lignosulfonate is more conducive to the formation of a stable NBS co-doped structure. Furthermore, sodium lignosulfonate has a strong dispersing effect, which can effectively inhibit the aggregation of nano-silicon and improve the uniformity of carbon layer coating. In another embodiment, the transition metal is at least one of iron, cobalt, and nickel, and the transition metal is mainly in the form of MN. xCoordination forms exist, where M represents a transition metal and x = 2~4.

[0032] In another embodiment, the nitrogen element in the porous carbon layer is pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen, and MN. x It exists in four forms, among which MN x The proportion is 20% to 50% of the total nitrogen content. The content of each doped element in the porous carbon layer is: transition metal 1 at.% to 5 at.%, nitrogen 3 at.% to 10 at.%, boron 1 at.% to 4 at.%, and sulfur 1 at.% to 3 at.%.

[0033] In some embodiments, the particle size of the nano-silicon is 50-200 nm, and the thickness of the porous carbon layer is 5-20 nm.

[0034] In some embodiments, the specific surface area of ​​the negative electrode material is 300~800 m². 2 / g, pore volume 0.8~2.5 cm³ 3 / g; and / or, the porous carbon layer has a three-level pore structure: micropores with a pore size <2 nm account for 15%-30% of the volume, mesopores with a pore size of 2~50 nm account for 50%~75% of the volume, and macropores with a pore size >50 nm account for 10%~25% of the volume.

[0035] In a second typical embodiment of this application, a method for preparing a negative electrode material is provided, which includes the following steps: S1. Dissolve sodium lignosulfonate in deionized water, then add transition metal salt, nitrogen source, and boron source, mix well to obtain precursor solution; S2. After functionalizing nano-silicon with amino or carboxyl groups, add it to the precursor solution, add a ligand, adjust the pH, and carry out a coordination self-assembly reaction to form a composite gel. S3. After heat treatment, the composite gel is pyrolyzed, acid-washed, and post-treated to obtain the negative electrode material.

[0036] Sodium lignosulfonate is used as a multifunctional precursor, possessing both an aromatic framework and sulfonic acid groups. During pyrolysis, it can directly form a conductive carbon network rich in defect and heteroatom doping sites. Simultaneously, the sulfonic acid groups can serve as a natural sulfur source, achieving uniform sulfur doping. Compared to systems where glucose and sodium sulfate provide carbon and sulfur sources respectively, the carbon and sulfur elements in sodium lignosulfonate are uniformly distributed at the molecular scale, which is more conducive to forming a stable NBS co-doped structure. Furthermore, sodium lignosulfonate has a strong dispersing effect, effectively inhibiting the aggregation of nano-silicon and improving the uniformity of carbon layer coating. Utilizing the pyrolysis characteristics of sodium lignosulfonate, a microporous-mesoporous-macroporous hierarchical structure is formed. In-situ growth and strong interfacial bonding: through surface hydroxylation and silane coupling agent modification, a covalently bonded interface is constructed on the nano-silicon surface. Molecular-level mixing and coordination of elements are achieved in the solution stage, realizing in-situ coordinated doping. This invention uses an aqueous system, suitable for industrial production.

[0037] In the coordination self-assembly process of this invention, transition metal ions can simultaneously undergo synergistic coordination with the hydroxyl, carboxyl, and sulfonic acid groups in sodium lignosulfonate, as well as the amino groups on the surface of nano-silicon, forming a uniform and stable three-dimensional network structure. Subsequent pyrolysis yields a porous doped carbon layer continuously coated on the surface of nano-silicon, achieving uniform dispersion of transition metal active sites.

[0038] In some embodiments, in step S1, the mass ratio of sodium lignosulfonate, transition metal, nitrogen source, and boron source is 1:(0.05~0.3):(0.2~0.8):(0.05~0.2).

[0039] In some embodiments, the transition metal salt is selected from at least one of ferric chloride, ferric nitrate, ferrous sulfate, cobalt chloride, cobalt nitrate, nickel chloride, and nickel nitrate; the nitrogen source is at least one of melamine, urea, dicyandiamide, and polyaniline; and the boron source is at least one of boric acid, borax, and phenylboronic acid.

[0040] In some embodiments, in step S2, functionalization includes: hydroxylating nano-silicon to obtain hydroxylated nano-silicon, dispersing the hydroxylated nano-silicon in a solvent, adding a silane coupling agent, reacting at 50-80°C for 4-8 hours under a protective atmosphere, and then post-processing to obtain amino or carboxyl functionalized nano-silicon; the silane coupling agent is γ-aminopropyltriethoxysilane or γ-carboxyethylsilane triol sodium salt.

[0041] In some embodiments, the ligand is ethylenediaminetetraacetic acid or citric acid; the pH adjustment is to adjust the pH to 4-7; and the coordination self-assembly reaction is carried out by stirring at 60-90°C for 2-5 hours. Through the coordination self-assembly reaction, transition metal ions form coordination bonds with the functional groups in sodium lignosulfonate and the surface groups of nano-silicon.

[0042] In some embodiments, in step S3, the heat treatment is performed at 80~120℃ for 2~6 hours; the pyrolysis involves first pre-carbonizing at 400~600℃ at a rate of 2~5℃ / min for 1~3 hours, and then carbonizing at 700~1000℃ at a rate of 5~10℃ / min for 2~4 hours. A stepwise pyrolysis strategy is adopted, with low-temperature pre-crosslinking to fix the doping elements and high-temperature carbonization to form a stable structure.

[0043] In a third typical embodiment of this application, a lithium battery is provided, comprising the negative electrode material as described above. The lithium battery has an initial discharge specific capacity ≥1800 mAh / g at 0.1C rate and an initial coulombic efficiency ≥83%; a capacity retention rate ≥85% after 800 cycles at 1C rate; and a capacity retention rate ≥70% at 5C rate.

[0044] The negative electrode material of this invention, after being compounded with graphite to a specific capacity of 500 mAh / g, is applied to a 4Ah soft-pack battery with an energy density ≥280 Wh / kg.

[0045] The beneficial effects of this application will be further illustrated below with reference to embodiments and comparative examples.

[0046] Example 1 This embodiment proposes an iron-nitrogen-boron-sulfur co-doped carbon / nano-silicon anode material, combined with... Figure 1 Its preparation method includes the following steps: S1. Preparation of composite precursor solution: Weigh 5.0 g of sodium lignosulfonate and add it to 100 mL of deionized water. Stir and dissolve in a 60℃ water bath. Then add 0.8 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) (0.16 g as Fe), 2.0 g of melamine, and 0.5 g of boric acid in sequence. Continue stirring for 2 hours until completely dissolved to obtain a uniform dark brown precursor solution.

[0047] S2. Surface functionalization of nano-silicon: 2.0 g of nano-silicon powder (particle size of 100 nm) was dispersed in 50 mL of piranha solution (mixed with concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1) and refluxed at 80 °C for 2 hours; after centrifugation and washing with water until neutral, the obtained hydroxylated nano-silicon was dispersed in 50 mL of anhydrous ethanol, and 3 mL of γ-aminopropyltriethoxysilane APTES was added. The mixture was refluxed at 75 °C for 6 hours under nitrogen protection. The product was washed with ethanol and dried under vacuum to obtain aminated nano-silicon.

[0048] S3. Coordination self-assembly: 1.0 g of the aminated nano-silicon prepared in step S2 was added to the precursor solution prepared in step S1 and ultrasonically dispersed for 30 minutes; then 0.5 g of ethylenediaminetetraacetic acid (EDTA) was added as a coordination agent, the pH was adjusted to 6.0 with ammonia water, and the reaction was stirred in an 80°C water bath for 3 hours to form a uniform brown gel.

[0049] S4. Pre-crosslinking treatment: Transfer the gel obtained in step S3 to an oven and heat-treat it at 100°C for 4 hours to promote intermolecular crosslinking and curing, thereby obtaining a pre-crosslinked product.

[0050] S5. Pyrolysis and doping: The pre-crosslinked product obtained in step S4 is placed in a tube furnace and subjected to programmed temperature pyrolysis under argon protection: first, the temperature is increased to 500℃ at 3℃ / min and held for 2 hours for pre-carbonization; then, the temperature is increased to 900℃ at 8℃ / min and held for 3 hours to complete carbonization and doping; the pyrolysis product is obtained.

[0051] S6. Post-treatment: The pyrolysis product was treated with 1M HCl solution at 80℃ for 6 hours to remove unreacted metal species; centrifuged and washed with water until neutral, and then vacuum dried at 80℃ for 12 hours to obtain the final anode material, denoted as Si@C-FeNBS-1.

[0052] XPS analysis of the Si@C-FeNBS-1 prepared in this embodiment revealed the following: Fe content was 2.3 at.%, N content was 6.2 at.%, B content was 1.8 at.%, and S content was 2.1 at.%.

[0053] Raman spectroscopy analysis of the Si@C-FeNBS-1 prepared in this embodiment yielded an ID / IG ratio of 1.05, indicating that the Si@C-FeNBS-1 prepared in this embodiment possesses a moderate defect density.

[0054] The Si@C-FeNBS-1 prepared in this embodiment was subjected to BET testing, and the specific surface area was found to be 480 m². 2 / g, pore volume 1.5 cm³ 3 / g.

[0055] Example 2 This embodiment proposes a cobalt-nitrogen-boron-sulfur co-doped carbon / nano-silicon anode material. The preparation method differs from Example 1 in that: in step S1 of this embodiment, cobalt chloride hexahydrate (CoCl2·6H2O) is used instead of ferric nitrate nonahydrate, and the amount of cobalt chloride hexahydrate added is 1.0 g (0.24 g as Co); in step S5, pyrolysis involves heating to 500°C at 3°C / min and holding for 2 hours for pre-carbonization, followed by heating to 850°C at 8°C / min and holding for 3 hours to complete carbonization and doping. The final anode material obtained in this embodiment is denoted as Si@C-CoNBS-1.

[0056] Example 3 This embodiment proposes a nickel-nitrogen-boron-sulfur co-doped carbon / nano-silicon anode material. The preparation method differs from that of Example 1 in that, in step S1 of this embodiment, nickel chloride hexahydrate (NiCl2·6H2O) is used instead of ferric nitrate nonahydrate, and urea is used instead of melamine. The amount of nickel chloride hexahydrate added is 0.9 g (0.22 g as Ni), and the amount of urea added is 2.5 g. The final anode material obtained in this embodiment is denoted as Si@C-NiNBS-1.

[0057] Example 4 This embodiment proposes a cobalt-iron bimetallic-nitrogen-boron-sulfur co-doped carbon / nano-silicon anode material. The preparation method differs from that of Example 1 in that: in step S1 of this embodiment, a mixture of ferric nitrate nonahydrate and cobalt chloride hexahydrate is used instead of ferric nitrate nonahydrate, the mixture containing 0.4 g of ferric nitrate nonahydrate and 0.5 g of cobalt chloride hexahydrate; in step S5, pyrolysis involves pre-carbonization by heating to 500°C at 3°C / min and holding for 2 hours, followed by heating to 750°C at 8°C / min and holding for 1 hour, and finally heating to 850°C at 8°C / min and holding for 3 hours to complete carbonization and doping. The final anode material obtained in this embodiment is denoted as Si@C-FeCoNBS-1.

[0058] Example 5 The Si@C-FeNBS-1 anode material prepared in Example 1 was mixed with commercial graphite at a mass ratio of 15:85 to obtain a composite anode material with a reversible specific capacity of approximately 500 mAh / g.

[0059] Comparative Example 1 This comparative example presents a nitrogen-boron-sulfur co-doped carbon / nano-silicon anode material. The difference in its preparation method compared to Example 1 is that ferric nitrate nonahydrate is not added in step S1 of this comparative example. The final anode material obtained in this comparative example is denoted as Si@C-NBS-1.

[0060] Comparative Example 2 This comparative example presents an iron-nitrogen-boron-sulfur co-doped carbon / nano-silicon anode material. The preparation method differs from Example 1 in that, in step S1 of this comparative example, 2.5g of glucose and 2.5g of sodium sulfate are used instead of 5.0g of sodium lignosulfonate. The final anode material obtained in this comparative example is denoted as Si@C-FeNB-S.

[0061] Comparative Example 3 This comparative example presents an iron-nitrogen-boron-sulfur co-doped carbon / nano-silicon anode material, the preparation method of which is as follows: S1. Preparation of composite precursor solution: Weigh 5.0 g of sodium lignosulfonate and add it to 100 mL of deionized water. Stir and dissolve in a 60℃ water bath. Then add 0.8 g of ferric nitrate nonahydrate (Fe(NO3)3·9H2O) (0.16 g as Fe), 2.0 g of melamine, and 0.5 g of boric acid in sequence. Continue stirring for 2 hours until completely dissolved to obtain a uniform dark brown precursor solution.

[0062] S2. Surface functionalization of nano-silicon: 2.0 g of nano-silicon powder (particle size of 100 nm) was dispersed in 50 mL of piranha solution (mixed with concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1) and refluxed at 80 °C for 2 hours; after centrifugation and washing with water until neutral, the obtained hydroxylated nano-silicon was dispersed in 50 mL of anhydrous ethanol, and 3 mL of γ-aminopropyltriethoxysilane APTES was added. The mixture was refluxed at 75 °C for 6 hours under nitrogen protection. The product was washed with ethanol and dried under vacuum to obtain aminated nano-silicon.

[0063] S3. Coordination self-assembly: 1.0 g of the aminated nano-silicon obtained in step S2 was added to the precursor solution obtained in step S1. After ultrasonic dispersion for 30 minutes, it was placed in a tube furnace and subjected to programmed temperature pyrolysis under argon protection: first, the temperature was increased to 500℃ at 3℃ / min and held for 2 hours for pre-carbonization; then, the temperature was increased to 900℃ at 8℃ / min and held for 3 hours to complete carbonization and doping; the pyrolysis product was obtained.

[0064] S4. Post-treatment: The pyrolysis product was treated with 1M HCl solution at 80℃ for 6 hours to remove unreacted metal species; centrifuged and washed with water until neutral, and then vacuum dried at 80℃ for 12 hours to obtain the final anode material, denoted as Si / C-FeNBS-Mix.

[0065] Test case (1) The negative electrode materials obtained in Examples 1-4 and Comparative Examples 1-3 were used to prepare batteries: The negative electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 95:2:3, and N-methylpyrrolidone (NMP) was used as a solvent to prepare a uniform slurry. The slurry was uniformly coated on the surface of a copper foil current collector, dried under vacuum at 80°C for 12 h, rolled, and punched into discs with a diameter of 12 mm as working electrodes. The active material loading was 1.0–2.0 mg / cm³. 2 The CR2032 button cell was assembled in an argon atmosphere glove box using lithium metal sheets as the counter electrode and reference electrode, Celgard 2400 polypropylene microporous membrane as the separator, and 1 mol / L LiPF6 dissolved in a mixed solvent of EC, DEC and EMC (volume ratio 1:1:1) as the electrolyte, with 2 wt% fluoroethylene carbonate (FEC) added as an additive.

[0066] The assembled CR2032 button half-cell was left to stand for 12 hours before electrochemical performance testing was conducted. Constant current charge-discharge tests were conducted using the LAND CT2001A battery testing system at 25±1℃ within a voltage range of 0.01–1.50 V (vs. Li / Li+). The initial charge-discharge test was performed at a rate of 0.1C (based on a theoretical capacity of 4200 mAh / g). Rate performance tests were then conducted sequentially at 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C rates, with 5 cycles at each rate. Long-cycle performance tests involved 800 consecutive charge-discharge cycles at 1C rate, and capacity retention was recorded.

[0067] Cyclic voltammetry (CV) tests were performed using a CHI 760E electrochemical workstation, scanning over a voltage range of 0.01–1.50 V (vs. Li / Li+) at a scan rate of 0.1 mV / s.

[0068] The initial coulombic efficiency is calculated as the ratio of the initial charge capacity to the initial discharge capacity; the capacity retention rate is calculated as the ratio of the discharge capacity at the end of the cycle to the initial cycle discharge capacity; the rate capacity retention rate is calculated as the ratio of the discharge capacity at 5C to the discharge capacity at 0.1C.

[0069] The electrode expansion rate was calculated by measuring the thickness change of the electrode before and after cycling: a digital thickness gauge was used to measure the thickness of the electrode before cycling (T0) and after completing 800 cycles at 1 C (T1). Five different locations were measured in parallel for each sample, and the average value was taken. The electrode expansion rate was calculated using the following formula: Electrode expansion rate (%) = (T1) T0) / T0×100% Where T0 is the electrode thickness before cycling and T1 is the electrode thickness after cycling.

[0070] The test results are shown in the table below.

[0071]

[0072] According to the results in the table above: The negative electrode materials of Examples 1-4 of this invention have the following characteristics: high specific capacity, with an initial discharge capacity of ≥1800 mAh / g at 0.1C; excellent cycle stability, with a capacity retention rate of ≥85% after 800 cycles at 1C; and good rate performance, with a capacity retention rate of ≥70% at 5C.

[0073] Compared to Comparative Example 1, Example 1, through iron doping, achieved an initial discharge capacity of 1880 mAh / g, higher than Comparative Example 1's 1620 mAh / g, with the initial coulombic efficiency increasing from 82.0% to 84.2%. The capacity retention after 800 cycles at 1C increased from 82.5% to 88.5%, and the capacity retention at 5C increased from 58% to 72%. This indicates that the introduction of the transition metal iron can significantly improve the electrochemical performance of the material: on the one hand, iron forms stable Fe-Nx active sites with nitrogen during pyrolysis, improving the electron transport capability of the carbon layer and reducing charge transfer impedance; on the other hand, the Fe-Nx structure can promote lithium ion adsorption and diffusion, improving interfacial reaction kinetics, thereby enhancing rate performance and cycle stability. Furthermore, the atomically dispersed iron active centers can induce the formation of more defect sites and active lithium storage sites, improving the material's reversible capacity. Therefore, this invention, by introducing a transition metal to construct an M-Nx active structure, is an important technical means to achieve high capacity, high rate capability, and long cycle performance.

[0074] Compared to Comparative Example 2, Example 1 used sodium lignosulfonate as both the carbon and sulfur source, while Comparative Example 2 used glucose as the carbon source and sodium sulfate as the sulfur source. Example 1 exhibited an initial discharge capacity of 1880 mAh / g, significantly higher than Comparative Example 2's 1700 mAh / g; the initial coulombic efficiency increased from 81.5% to 84.2%; the capacity retention after 800 cycles at 1C increased from 83.2% to 88.5%; and the capacity retention at 5C rate increased from 65% to 72%. Sodium lignosulfonate possesses both an aromatic framework and sulfonic acid groups, enabling the direct formation of a conductive carbon network rich in defect and heteroatom doping sites during pyrolysis. Simultaneously, the sulfonic acid groups can serve as a natural sulfur source, achieving uniform sulfur doping. Compared to systems where glucose and sodium sulfate provide the carbon and sulfur sources respectively, the uniform distribution of carbon and sulfur at the molecular scale in sodium lignosulfonate is more conducive to the formation of a stable NBS co-doped structure. Furthermore, sodium lignosulfonate has a strong dispersing effect, which can effectively inhibit the aggregation of nano-silicon and improve the uniformity of carbon layer coating. Therefore, this invention utilizes sodium lignosulfonate as a multifunctional precursor, which not only simplifies the raw material system but also significantly improves the structural stability and electrochemical performance of the material.

[0075] Compared with Comparative Example 3, Example 1 employed a coordination self-assembly process to construct a composite gel followed by pyrolysis, while Comparative Example 3 simply involved mechanically mixing aminated nano-silicon with the precursor before direct pyrolysis. Example 1 achieved an initial discharge capacity of 1880 mAh / g, higher than Comparative Example 3's 1550 mAh / g; the initial coulombic efficiency increased from 78.5% to 84.2%; the capacity retention after 800 cycles at 1C increased from 76.0% to 88.5%; and the capacity retention at 5C rate increased from 52% to 72%. These results demonstrate that the coordination self-assembly step plays a crucial role in material performance. During coordination self-assembly, transition metal ions can simultaneously coordinate with the hydroxyl, carboxyl, and sulfonic acid groups in sodium lignosulfonate, as well as the amino groups on the surface of nano-silicon, forming a uniform and stable three-dimensional network structure. Subsequent pyrolysis yields a continuously porous doped carbon layer continuously coating the surface of nano-silicon, achieving uniform dispersion of transition metal active sites. In contrast, simple mechanical mixing struggles to form stable interfaces, and during pyrolysis, problems such as silicon particle agglomeration, uneven carbon layer coating, and localized enrichment of transition metals easily arise, leading to structural instability and rapid capacity decay during cycling. Therefore, this invention employs a coordination self-assembly strategy to achieve molecular-level uniform composites of nano-silicon, sodium lignosulfonate, and transition metal precursors, representing a key innovation in improving the material's structural stability and electrochemical performance.

[0076] (2) The composite negative electrode material of Example 5 was used to prepare a battery: The composite negative electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were mixed at a weight ratio of 95:2:3, and N-methylpyrrolidone (NMP) was used as a solvent to prepare a uniform slurry. The slurry was uniformly coated on the surface of a copper foil current collector, and after vacuum drying at 80°C for 12 h, it was rolled to obtain a negative electrode sheet. A commercial NCM811 positive electrode sheet was used, and the N / P ratio was controlled at 1.05 to 1.15. A 1 M LiPF6 / EC:DEC:EMC (1:1:1) electrolyte was used. A soft-pack lithium-ion battery with a rated capacity of 4 Ah was assembled. The soft-pack lithium-ion battery was tested. The test results showed that the initial coulombic efficiency was ≥90%; the capacity retention rate at 0.5C discharge was ≥95%; the capacity retention rate at 1C after 500 cycles was ≥80%; and the battery energy density reached more than 280Wh / kg.

[0077] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0078] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A negative electrode material, characterized in that, It includes a three-dimensional carbon network framework and core-shell particles embedded in the three-dimensional carbon network framework. The core-shell particles include a nano-silicon core and a porous carbon shell layer covering the nano-silicon core. The porous carbon layer contains doping elements, including transition metals, nitrogen, boron, and sulfur.

2. The negative electrode material according to claim 1, characterized in that, Both the three-dimensional carbon network framework and the porous carbon shell are formed by the pyrolysis of sodium lignosulfonate.

3. The negative electrode material according to claim 1, characterized in that, The transition metal is at least one of iron, cobalt, and nickel, and the transition metal mainly exists in the form of M-Nx coordination, where M represents the transition metal and x = 2~4.

4. The negative electrode material according to claim 1, characterized in that, In the porous carbon layer, nitrogen exists in four forms: pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen, and M-Nx, among which MN x It accounts for 20% to 50% of the total nitrogen content.

5. The negative electrode material according to claim 1, characterized in that, The content of each doped element in the porous carbon layer is as follows: transition metal 1 at.%~5 at.%, nitrogen 3 at.%~10 at.%, boron 1 at.%~4 at.%, sulfur 1 at.%~3 at.%.

6. The negative electrode material according to claim 1, characterized in that, The nano-silicon has a particle size of 50~200 nm, and the porous carbon layer has a thickness of 5~20 nm.

7. The negative electrode material according to claim 1, characterized in that, The specific surface area of ​​the negative electrode material is 300~800m². 2 / g, pore volume 0.8~2.5 cm³ 3 / g; and / or, the porous carbon layer has a three-level pore structure: micropores with a pore size <2 nm account for 15%-30% of the volume, mesopores with a pore size of 2~50 nm account for 50%~75% of the volume, and macropores with a pore size >50 nm account for 10%~25% of the volume.

8. A method for preparing a negative electrode material as described in any one of claims 1-7, characterized in that, It includes the following steps: S1. Dissolve sodium lignosulfonate in deionized water, then add transition metal salt, nitrogen source, and boron source, mix well to obtain precursor solution; S2. After functionalizing nano-silicon with amino or carboxyl groups, add it to the precursor solution, add a ligand, adjust the pH, and carry out a coordination self-assembly reaction to form a composite gel. S3. After heat treatment, the composite gel is pyrolyzed, acid-washed, and post-treated to obtain the negative electrode material.

9. The method for preparing the negative electrode material according to claim 8, characterized in that, In step S1, the mass ratio of sodium lignosulfonate, transition metal, nitrogen source, and boron source is 1:(0.05~0.3):(0.2~0.8):(0.05~0.2).

10. The method for preparing the negative electrode material according to claim 8, characterized in that, The transition metal salt is selected from at least one of ferric chloride, ferric nitrate, ferrous sulfate, cobalt chloride, cobalt nitrate, nickel chloride, and nickel nitrate; And / or, the nitrogen source is at least one of melamine, urea, dicyandiamide, and polyaniline; And / or, the boron source is at least one of boric acid, borax, and phenylboronic acid.

11. The method for preparing the negative electrode material according to claim 8, characterized in that, In step S2, the functionalization includes: hydroxylating nano-silicon to obtain hydroxylated nano-silicon, dispersing the hydroxylated nano-silicon in a solvent, adding a silane coupling agent, reacting at 50-80°C for 4-8 hours under a protective atmosphere, and then post-processing to obtain amino or carboxyl functionalized nano-silicon; the silane coupling agent is γ-aminopropyltriethoxysilane or γ-carboxyethylsilane triol sodium salt.

12. The method for preparing the negative electrode material according to claim 8, characterized in that, The ligand is ethylenediaminetetraacetic acid or citric acid; the pH adjustment is to adjust the pH to 4-7; the coordination self-assembly reaction is carried out by stirring at 60-90℃ for 2-5 hours.

13. The method for preparing the negative electrode material according to claim 8, characterized in that, In step S3, the heat treatment is performed at 80~120℃ for 2~6 hours; the pyrolysis is performed by first heating at 2~5℃ / min to 400~600℃ for pre-carbonization for 1~3 hours, and then heating at 5~10℃ / min to 700~1000℃ for carbonization for 2~4 hours.

14. A lithium battery, characterized in that, It includes the negative electrode material as described in any one of claims 1-8.

15. The lithium battery according to claim 14, characterized in that, The lithium battery has an initial discharge specific capacity of ≥1800 mAh / g and an initial coulombic efficiency of ≥83% at 0.1C rate; a capacity retention rate of ≥85% after 800 cycles at 1C rate; and a capacity retention rate of ≥70% at 5C rate.